Porphyromonas gingivalis lipopolysaccharide activates platelet Cdc42 and promotes platelet spreading and thrombosis. Issue 11 (1st July 2019) - Senini, Vincent; Amara, Umme; Paul, Manoj; Kim, Hugh
Abstract: Background: Periodontitis confers an increased risk for cardiovascular diseases, including thrombosis. However, the molecular mechanisms that potentially link periodontitis with thrombosis are undefined. Here we test the hypothesis that Gram‐negative periodontal infection promotes pathological platelet activation and amplifies shape change. We focus specifically on lipopolysaccharide (LPS) signaling to platelets. Methods: Platelets were isolated from blood samples and allowed to spread on coverslips in the presence or absence of LPS purified from the periodontal pathogen Porphyromonas gingivalis . Platelets were fixed and stained with Alexa‐488‐phalloidin to label the actin cytoskeleton. The degree of platelet spreading and shape change was quantified by confocal microscopy. In a translational pilot study, blood samples were obtained from human subjects exhibiting generalized severe periodontitis (SP) or healthy periodontium (HP). Rotational thromboelastometry was used to quantify the rate of clot formation via the intrinsic coagulation pathway. Results: LPS‐treated platelets exhibited significantly ( P  < 0.05) greater spreading and higher numbers of actin‐rich filopodia (cell extensions) than controls. We also found that LPS stimulation of platelets promoted the activation of Cdc42, the small GTPase responsible for filopodia formation. Exposure of whole blood samples to LPS significantly ( P  < 0.05) reduced clotting times. Blood from SP patients clotted significantly ( P  < 0.05) more rapidly and exhibited shorter partial thromboplastin times compared with HP controls. Conclusions: This is the first study to suggest a mechanism by which LPS stimulation drives Cdc42 activation and platelet spreading. These data are consistent with the notion that periodontitis promotes accelerated clot formation and an increased risk of thrombosis.